2014
DOI: 10.1128/aac.03509-14
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Profile in Patients with Acute Bacterial Skin and Skin Structure Infections Receiving Tedizolid or Linezolid: Findings from the Phase 3 ESTABLISH Clinical Trials

Abstract: c Tedizolid, the active moiety of tedizolid phosphate, is a recently approved oxazolidinone antibacterial with activity against a wide range of Gram-positive pathogens, including resistant strains such as methicillin-resistant Staphylococcus aureus. To date, 6 days of 200 mg tedizolid once daily has been shown to be noninferior to 10 days of 600 mg linezolid twice daily in two randomized, double-blind phase 3 trials (ESTABLISH-1 and ESTABLISH-2) for the treatment of patients with acute bacterial skin and skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…This outcome was observed independently of the differences in exposure times (31,32). Pooled data from these clinical trials suggested a potentially clinically relevant difference in terms of adverse platelet outcomes between linezolid and tedizolid, but the authors concluded that longer-term studies were necessary to ascertain this possibility (59).…”
Section: Discussionmentioning
confidence: 99%
“…This outcome was observed independently of the differences in exposure times (31,32). Pooled data from these clinical trials suggested a potentially clinically relevant difference in terms of adverse platelet outcomes between linezolid and tedizolid, but the authors concluded that longer-term studies were necessary to ascertain this possibility (59).…”
Section: Discussionmentioning
confidence: 99%
“…In the tedizolid post-approval period, the risk of thrombocytopenia was over 30 times higher with both tedizolid and linezolid as compared with adverse event reports from other medications. In the period prior to tedizolid approval, the risk of thrombocytopenia was 12 times higher with linezolid (5,14).…”
Section: Discussionmentioning
confidence: 99%
“…A "substantially low platelet count" has been defined as <75% of the lower limit of normal or baseline, where the lower limit of normal (LLN) is 150,000 cells/mm 3 , resulting in a platelet count of 112,500 cells/mm 3 (3,5,15). However, a lower threshold of less than 100,000 cells/mm 3 is considered clinically relevant and has been used to operationally define thrombocytopenia (5,14).…”
Section: Discussionmentioning
confidence: 99%
“…Tigecycline has major limitations as outlined in Table , and sparse clinical data support the use of these alternative agents for VRE bacteremia. Tedizolid is a new oxazolidinone that appears to be less myelosuppressive than linezolid, and thus is an attractive candidate for use in HSCT recipients. However, animal models have demonstrated that the efficacy of tedizolid is markedly reduced in the setting of neutropenia, thus making it a less attractive alternative for VRE infections in neutropenic patients.…”
Section: Vrementioning
confidence: 99%